Campanulaceae endémicas del Perú - León, Blanca (2006)
The Campanulaceae are represented in Peru by 11 genera and around 180 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly shrubs and herbs. Here we recognize 32 endemic species in three genera. Siphocampylus and Centropogon account for the largest number of endemic species. Endemic Campanulaceae are found mostly in the Very Humid Montane Forests region, between 800 and 3600 m elevation. We applied IUCN categories and criteria to 23 species. Nine endemic species have been recorded within the Peruvian parks system.